2012
DOI: 10.1111/j.2047-6310.2012.00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered red blood cell distribution width in overweight adolescents and its association with markers of inflammation

Abstract: RDW is elevated in overweight and reflects the inflammatory state. RDW potentially represents an additional and cost-effective tool to indicate inflammation. Future studies are needed to understand the differential influences of nutrition and overweight on RDW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 39 publications
(42 reference statements)
5
49
1
5
Order By: Relevance
“…Increased RDW also may be a useful marker for the assessment of liver function, with associations noted for both non-alcoholic steatohepatitis and fibrosis [27], and HBV induced liver cirrhosis [28]. Underpinning RDW associations with the diverse array of disease is a likely link to increased inflammation [3,29] and disrupted erythropoiesis. RDW has been suggested as a marker of oxidative stress or physiological reserve [25], which suggests that under acute cellular stress and resultant tissue hypoxia, there would be increased production and release of mature erythrocytes into the peripheral blood stream.…”
Section: Discussionmentioning
confidence: 99%
“…Increased RDW also may be a useful marker for the assessment of liver function, with associations noted for both non-alcoholic steatohepatitis and fibrosis [27], and HBV induced liver cirrhosis [28]. Underpinning RDW associations with the diverse array of disease is a likely link to increased inflammation [3,29] and disrupted erythropoiesis. RDW has been suggested as a marker of oxidative stress or physiological reserve [25], which suggests that under acute cellular stress and resultant tissue hypoxia, there would be increased production and release of mature erythrocytes into the peripheral blood stream.…”
Section: Discussionmentioning
confidence: 99%
“…Proper erythropoiesis is the function of a complex interaction between numerous signaling pathways, which in turn is affected by inflammation [22][23][24][25] . It is now well established that many disorders, both acute and chronic, are accompanied by an inflammatory reaction 26,27 . The influence of oxidative stress on RDW variation however seems to differ from that of inflammation.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Some evidence shows that RDW acts quite similar to wellknown inflammatory markers such as leukocytosis and elevated C-reactive protein (10). Nonetheless, this seems to be an oversimplification of the role of RDW.…”
Section: Discussionmentioning
confidence: 99%
“…Although in our study RDW was shown to be independent of other factors, such as hemoglobin levels and malignancy, some probable confounders, such as iron deficiency anemia, recent treatment by iron supplements, and megaloblastic anemia, might have inadvertently affected the results; however, being an acute disease process, it seems improbable for PE mortality to be directly affected by the hemoglobin level. In addition, the PE-related inflammatory state may confound the relationship between RDW and long-term mortality (10). Further studies designed to control for these factors from the beginning of the patient selection process are suggested for a more robust confirmation of the observed association between RDW and long-term PE mortality.…”
Section: Discussionmentioning
confidence: 99%